Pharmacognostic and Antioxidant Properties of Dracaena sanderiana Leaves - Mei Gee Ong; Siti Nur Aishah Mat Yusuf; Vuanghao Lim (Antioxidants, 2016)
Endogenous and exogenous antioxidants are used to neutralise free radicals and protect the body from free radicals by maintaining the redox balance. The antioxidant properties of Dracaena sanderiana leaves were evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay, and the total phenolic and flavonoid contents were measured. The classes of secondary metabolites were evaluated through pharmacognostic studies, and active compounds were identified by gas chromatography mass-spectrometry (GC-MS). All ethanol-water extracts and D. sanderiana leaf powder were positive for tannins, saponins, terpenoids, cardiac glycosides, and quinones. Flavonoids were present in 100%, 80%, 60%, and 40% ethanol extracts (E100, E80, E60, and E40). E100 showed the highest total flavonoid content, whereas E60 extract showed the highest antioxidant activity and total phenolic content. GC-MS revealed the presence of glycerol, 2,3-dihydro-3,5-dihydroxy-6-methyl-(4H)-pyran-4-one, n-dodecanoic acid, tetradecanoid acid, (n-) hexadecanoid acid, and n-octadecanoic acid in the E60 extract.